Safety of laparoscopic hepatectomy in patients with severe comorbidities ‐ A propensity score matched analysis. (22nd July 2021) - Heise, Daniel; Bednarsch, Jan; Kroh, Andreas; Eickhoff, Roman; Coolsen, Marielle M. E.; van Dam, Ronald; Lang, Sven Arke; Neumann, Ulf Peter; Ulmer, Florian
Abstract: Background: Laparoscopic hepatectomy (LH) is nowadays considered as the standard of care for various liver malignancies. However, studies focusing on perioperative outcome after LH in patients with severe comorbidities are still sparse. Methods: 247 patients, who underwent LH between January 2016 and March 2020 at European surgical center Aachen Maastricht (ESCAM) were retrospectively analyzed regarding surgical outcome. All patients were categorized according to the ASA guidelines and a propensity score matched (PSM) analysis was performed to compare patients with severe comorbidities with patients with minor or no comorbidities. Results: After PSM, no statistically significant differences regarding clinical characteristics were observed. We performed major resections in 26.4% of h‐ASA (ASA > 2) patients and 19.4% of l‐ASA (ASA≤2) patients, respectively ( P  = .322). Overall morbidity (Clavien‐Dindo≥1) was observed more frequently in the h‐ASA group (h‐ASA: 25.0% vs. l‐ASA: 8.3%; P  = .007) while analysis of major morbidity (Clavien‐Dindo≥3b) showed a non‐significant tendency for more complications in h‐ASA patients (h‐ASA: 8.3% vs. l‐ASA: 1.4%; P  = .053). A subgroup analysis identified major resection (HR = 5.05; P  = .006) as an independent risk factor for the occurrence of any postoperative complication and chronic kidney disease (HR = 22.59; P  = .030) and liver fibrosis (HR = 30.16; P  = .031) as risk factors for the occurrence of major complications in h‐ASA patients. Conclusion: LH in patients with severe systemic comorbidities shows a strong tendency towards an increased rate of major complications. Careful patient selection with respect to the planned extent of resection and the presence of chronic kidney disease and liver fibrosis should be performed to improve perioperative results. Abstract : Highlight Heise and colleagues compared the short‐term results of laparoscopic hepatectomy in patients with and without severe systemic comorbidities stratified by the ASA‐score. Patients with ASA ≥III showed a strong tendency towards an increased rate of major complications. Risk factors were the presence of chronic kidney disease and liver fibrosis.